Pengaruh Pertumbuhan Ekonomi, Inflasi Dan Pengangguran Terhadap Kemiskinan Di Indonesia Tahun 2014-2023 - Fitri Ani Dwi Lusiana; Fitri Salsabila; Muhammad Kurniawan (Wawasan : Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2024)
This research aims to determine the influence of Economic Growth, Inflation and Unemployment on Poverty in Indonesia in 2014-2023, either partially or simultaneously. The research approach is a quantitative approach. The population in this study is data on Economic Growth, Inflation, Unemployment and Poverty in Indonesia for 2014-2023. Data collection techniques with documentation, data collection tools are in the form of documentation obtained from the Central Statistics Agency (BPS). To process the data, use EVIEWS 10. The results of this research show that Economic Growth, Inflation and Unemployment partially have a positive influence on Poverty in Indonesia. Economic Growth, Inflation and Unemployment simultaneously have a significant positive effect on poverty in Indonesia. Inflation has an insignificant positive effect on poverty in Indonesia in 2014-2023 using a confidence level of 95% or ɑ = 0.05. Unemployment has a positive and insignificant effect on poverty in 2014-2023 using a confidence level of 95% or ɑ = 0.05. Economic Growth, Inflation and Unemployment together have a positive effect on Poverty in Indonesia using a confidence level of 95% or with alpha (ɑ) = 0.05.